Prayer Guide Tool for the Deaf Using Gyroscope Sensor and HC-12 - Muhammad Mahda Winasis; Hanifah Rahmi Fajrin; Wisnu Kartika (ELKHA : Jurnal Teknik Elektro, 2022)
Congregational prayer for the Muslim is a prayer done together at least consisting of an Imam (leader of congregation) and Makmum (participants/followers). In carrying out congregational prayers, the deaf frequently struggle to follow the Imam's movement. Therefore, a tool is required to help the deaf in performing congregational prayers. In the previous tools, there are several shortcomings in terms of short data transmission and disability to distinguish the vibrations in each prayer movement.  The short data transmission distance causes the deaf to be less optimal in carrying out congregational prayers because vibration notifications is not conveyed from Imam to Makmum. In this study, a tool will be designed to guide the deaf when performing congregational prayers. This tool uses the HC-12 wireless module to transmit data from the Imam’s device to Makmum’s. Changes in prayer position will be detected by the MPU 6050 gyroscope sensor. The tool will send notifications to the deaf Makmum in separate vibrations for any changes in the Imam 's movement. After testing on 30 different people, the accuracy value is 85.3% and the tool can transmit data at a maximum distance of 30 meters. As a result, the tool can assist the deaf in performing worship services.